Notching Philanthropy: BUILDING SOCIAL CAPITAL revitalize NATIONS CRISIS IN THE MIDDLE OF MORAL NATION - I Ketut Margi (Universitas Pendidikan Ganesha, 2016)
The Indonesian people are faced with a situation 'uncertainty moral' (indeterminancy of moral), a gray line of morality, one point of moral ambiguity, or the Indonesian nation was deep in the valley